O discurso acadêmico sobre gravidez na adolescência: uma produção ideológica? - Calazans, Gabriela Junqueira (2000)
This work integrates to the production by NEGRI - PUC-SP [Centre for the Studies on Gender, Race and Age] an study about the academic discourse on pregnancy among adolescents and is added to the efforts by NEGRI s members to study the Social Construction about child and adolescent in Brazil. We focused the study of age relations in a social context where conflicts of values among different ages are held in the negotiation of cultural models and life styles. Thus, the study of the academic discourse undertaken by this research didn t intend to develop internal critique about its scientific validation but instead, it intended to interpret the ways such a discourse embodies to its shape the dominant values representations about age relations. In order to do so, we analysed the academic articles published in Brazilian scientific periodicals from 1990 to 1999. This work focused the examination of contemporary trends as indicated in thematic literature and aimed to reinterpret the interpretations given by the texts about adolescent pregnancy enlightened by the concept of ideology as proposed by Thompson. In the methodological sphere we searched for integrating the techniques given by Content Analysis as presented by Bardin and undertaken by Rosemberg, to the theoretical-methodological reference given by Depth Hermeneutics as developed by Thompson. We observed the Health Sciences disciplinary field as the main context for the production and circulation of discourses about pregnancy among adolescents. We confirmed the trend of their comprehension in the sphere of a social problem as previously pointed out by critical literature on pregnancy during adolescence. As one of the linguistic resources for the expression of this problem we identified the statement of negative consequences to the young girls related to the spheres of health, psycho-emotional life and social-economical disadvantages. We corroborated the notion of transition as a dominant conception about adolescence. The use of this notion usually engaged an individual sphere which involves several fields of life (psychic, biological, sexual and social), and a social sphere, regarded to the transformations in the cultural models for adolescence which embody sexual behaviour and values related to the morality and sexual-emotional life. In the articles analysed we also observed a close relation established between the occurring of pregnancy and the transformations in the cultural models for adolescent s sexual behaviour and morality